Post-Event restoration strategy for coupled distribution-transportation system utilizing spatiotemporal flexibility of mobile emergency generator and mobile energy storage system - Erenoglu, Ayse Kubra; Erdinc, Ozan (ELSEVIER SCIENCE SA, 2021)
In this paper, a mixed integer quadratic programming (MIQCP) based post-event distribution restoration framework in response to high impact low probable events is propounded to maintain the power supply continuity of critical loads particularly in emergency conditions. Mobile power sources (MPSs) including mobile energy storage system (MESS) and mobile emergency generator (MEG) are considered as grid-support services in resiliency enhancement strategy due mainly to their spatiotemporal flexibility. Power system constraints are modelled according to the linearized DistFlow equations; on the other hand, traffic congestion is also considered while directing MPSs from staging locations to damaged areas. Repair crew dispatching schedule for maximizing the objective function is provided in a deterministic fashion. Numerical results based on the conducted case studies on modified version of the 15-bus distribution system show the capabilities of the model. Hereby power demand of all critical loads is served after an optimal allocation of MPS even though the damages are not completely cleared in the branches. Further, the decisions are close to what can be realistically expected in practical implementation, that fast-responded resources are exploited depending on traffic-related constraints and economic issues.
Keywords: Distribution system; Mobile emergency generator; Mobile energy storage system; Mobile power sources; Optimization; Power system resiliency; RESILIENCE; RELIABILITY; ALLOCATION; RESOURCES; Engineering